Collecting, generating and analyzing national statistics with AI: what benefits and costs? - Maria J. Rim; Youngsun Kwon (International Telecommunications Society (ITS), 2023)
The paper addresses the increasing adoption of digital transformation in public sector organizations, mainly focusing on its impact on national statistical offices. The emergence of data-driven strategies powered by artificial intelligence (AI) disrupts the conventional labourintensive approaches of NSOs. This necessitates a delicate balance between real-time information and statistical accuracy, leading to exploring AI applications such as machine learning in data processing. Despite its potential benefits, the cooperation between AI and human resources requires in-depth examination to leverage their combined strengths effectively. The paper proposes an integrative review and multi-case study approach to comprehensively contribute to a deeper understanding of the benefits and costs of AI adoption in national statistical processes, facilitate the acceleration of digital transformation, and provide valuable insights for policymakers and practitioners in optimizing the use of AI in collecting, generating and analyzing national statistics.
Keywords: 330; Digital transformation; national statistics; artificial intelligence; human resources; data-driven strategy